Kazakhs in the Regional System of Governance in the Second Half of the 19 th Century - A, Sultangalieva G. (Farabi Journal of Social Sciences, 2019)
Abstract. Stuff of regional and district administrations included senior andjunior officials for special assignments. Kazakhs representatives had the right to hold posts of junior officials for special assignments. The principle of cooptation of the Kazakhs for the position, the issue of the social security (salary, pension, awards, etc.) of junior officials for special assignments and their educational level, functional responsibilities and activities were all that practically have not been studied. The paper is based on documentary materials extracted from the Central State Archive of the Republic of Kazakhstan. On this basis, the study raises not only the issue of a new stratum of personalities in the new history of Kazakhstan, but also poses new challenges of a comparative study of imperial administration practices in the regions of multinational Empire.